2019
DOI: 10.1515/jcim-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural remedies to treat oral diseases among female patients in Al Madinah, western Saudi Arabia

Abstract: Background The study aimed to investigate natural remedies use (NRU) for oral diseases among female patients. Methods Dental patients attending the female section of Taibah University Dental Hospital were invited to complete an online questionnaire which explored demographic data, and pattern of NRU for oral diseases. Results A total of 540 patients participated in the survey. A total of 232 patients (43%) used natural remedies to treat oral diseases. The most commonly cited reasons for NRU were financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Buchenavia tomentosa and Chrysobalanus icaco, natural plants from central Brazil, showed promising antifungal activity for Candida albicans, reducing its ability to form biofilms, hyphae and adhere to oral epithelial cells [23,35,36]. Just like cloves, used since antiquity to relieve dental pain and to treat oral candidiasis and herpes infections [8].…”
Section: Flowchart Of the Selection And Results Of The Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Buchenavia tomentosa and Chrysobalanus icaco, natural plants from central Brazil, showed promising antifungal activity for Candida albicans, reducing its ability to form biofilms, hyphae and adhere to oral epithelial cells [23,35,36]. Just like cloves, used since antiquity to relieve dental pain and to treat oral candidiasis and herpes infections [8].…”
Section: Flowchart Of the Selection And Results Of The Papersmentioning
confidence: 99%
“…Regarding the feeling of dry mouth and halitosis, the study by Dar-Odeh et al [8] reported the use of olive oil for dry mouth and halitosis and tahini (sesame paste) for dry mouth and oral ulcers. Veloso et al reported that pomegranate and jucá (Libidibiaferrea) can potentially combat microorganisms related to halitosis, as the studied extracts inhibited oral microorganisms that produce volatile sulfur compounds [25].…”
Section: Flowchart Of the Selection And Results Of The Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It is important to highlight the importance of taking a thorough medical history from patients regarding the history of allergies and to exclude a positive history of food or drug allergy before prescribing any medications particularly antibiotics and nonsteroidal antiinflammatory drugs. 17 …”
Section: Discussionmentioning
confidence: 99%
“…It is well-established now that many of these women are basically immigrants and have a language barrier complicated by low education, causing many of them to be illiterate in Arabic and/or English, and hence incapable of communicating or relaying their fears and expectations to their care givers [10]. They may also have financial barriers [17] and transportation problems [2], making access to healthcare limited and jeopardized. The findings of this study confirm the high prevalence of dental caries, as 86–89% (according to the age group) of women had carious teeth.…”
Section: Discussionmentioning
confidence: 99%